2001
DOI: 10.1177/002215540104900807
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Necrosis Factor-alpha (TNF-α) in Skeletal Muscle Regeneration

Abstract: The role of tumor necrosis factor-alpha (TNF-α), an important mediator of the inflammatory response after injury, was investigated in regenerating skeletal muscle. The pattern of expression of TNF-α during muscle regeneration was examined by immunohistochemistry in tissue sections of crush-injured or transplanted muscle autografts and in primary cultures of adult skeletal muscle. TNF-α was highly expressed in injured myofibers, inflammatory cells, endothelial cells, fibroblasts, and mast cells. Myoblasts and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 80 publications
3
90
1
Order By: Relevance
“…concentrationdependent. Other studies showed that repeated doses from 100 to 500 µg/kg of TNF-α had resulted in muscle protein loss or apoptosis (24,40). That would explain the inability of short pouches to elongate in G.B, as the (41).This note matches with the present study where infiltrated inflammatory cells in the area of tumors and around necrotic tissue were intensely expressed in groupB i.e.…”
Section: -Protective and Promising Myogenic Effect Of Two Thymoquinonsupporting
confidence: 91%
“…concentrationdependent. Other studies showed that repeated doses from 100 to 500 µg/kg of TNF-α had resulted in muscle protein loss or apoptosis (24,40). That would explain the inability of short pouches to elongate in G.B, as the (41).This note matches with the present study where infiltrated inflammatory cells in the area of tumors and around necrotic tissue were intensely expressed in groupB i.e.…”
Section: -Protective and Promising Myogenic Effect Of Two Thymoquinonsupporting
confidence: 91%
“…CAME was more effective in suppressing the serum level of TNF-a than indomethacin. TNF-a plays several important roles in inflammation based on its appearance at the inflammatory site and ability to induce certain mechanisms including activation and chemotaxis of leukocytes, expression of adhesion molecules on neutrophils and endothelial cells, and regulation of the secretion of other pro-inflammatory cytokines (Cha et al, 2011;Collins et al, 2001;Park et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Following muscle injury, the early invading neutrophil and macrophage populations express TNF-␣ (15,137), suggesting that the cytokine may contribute to the early inflammatory stages that precede muscle regeneration. TNF-␣ levels in muscle following acute injury peak at 24 h postinjury, which indicates that TNF-␣ production is most tightly coupled with the Th1 inflammatory response in injured muscle (126).…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 99%